Digital Fluency in Education: Integrating Technology for Effective Teaching and Learning - Muhammad Yasin (Penelitian dan Pengembangan Ilmu, 2024)
Digital fluency and collaboration skills in the context of technology-based learning are areas of increasing importance in modern education. This study aims to investigate the role of digital fluency skills in improving collaboration between teachers and students in technology-based learning. The research method used included a literature review of articles from relevant international databases. The results of the discussion highlight the importance of digital fluency skills in facilitating effective collaboration between teachers and students in technology-based learning. The implication of this research is the need for a holistic approach in developing digital fluency skills, as well as the importance of support and collaboration between stakeholders to overcome challenges in implementing effective collaboration in technology-based learning.